Long Term Collaborative Business Relationships: The Impact of Trust and C3 Behaviour - Humphries, Andrew; Wilding, Richard D. (Westburn Publishers, 2004)
Long-term, collaborative business relationships are like marriages where tolerance, forbearance and some reduction of freedom as well as innovation are necessary to ensure success. Trust and co-operative behaviours are known to be essential ingredients in securing an environment of continuous improvement but, how they are correlated has yet to be tested. The paper describes a research project within a sample of long-term monopoly businesses as a novel approach to bringing trust and cooperation, co-ordination and collaboration (C3 Behaviour) into sharper focus without competitive distractions. It was found that a correlation between trust and C3 Behaviour and the success of the collaborative relationship exists.